1997
DOI: 10.2166/wst.1997.0754
|View full text |Cite
|
Sign up to set email alerts
|

Enterococci in the New Zealand environment: implications for water quality monitoring

Abstract: Faecal enterococci ecology outside the host is of great relevance when using these organisms as indicators of water quality. As a complement to New Zealand epidemiological studies of bathing water quality and health risk, a study of the environmental occurrence of these organisms has been undertaken. Specific concerns over the use of enterococci derive from the unique situation in New Zealand which has few chlorinated sewage effluents, a high ratio of grazing animals to humans, and significant inputs of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 0 publications
4
42
1
Order By: Relevance
“…Other aquatic macrophytes that have been identified as sources of enterococci include decaying seaweed (11,131,167). In New Zealand, Anderson et al (11) observed that the densities of enterococci in drifting seaweed exceeded those in seawater by 2 to 4 orders of magnitude; Grant et al (131) found densities of enterococci as high as a 450,000 most probable number (MPN)/100 g in a marsh in southern California.…”
Section: Environmental Reservoirs and Extraenteric Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other aquatic macrophytes that have been identified as sources of enterococci include decaying seaweed (11,131,167). In New Zealand, Anderson et al (11) observed that the densities of enterococci in drifting seaweed exceeded those in seawater by 2 to 4 orders of magnitude; Grant et al (131) found densities of enterococci as high as a 450,000 most probable number (MPN)/100 g in a marsh in southern California.…”
Section: Environmental Reservoirs and Extraenteric Habitatsmentioning
confidence: 99%
“…In New Zealand, Anderson et al (11) observed that the densities of enterococci in drifting seaweed exceeded those in seawater by 2 to 4 orders of magnitude; Grant et al (131) found densities of enterococci as high as a 450,000 most probable number (MPN)/100 g in a marsh in southern California. In addition to seaweed, recent studies have expanded the occurrence of enterococci to submerged aquatic vegetation (SAV) (mostly Hydrilla verticillata) (15,16).…”
Section: Environmental Reservoirs and Extraenteric Habitatsmentioning
confidence: 99%
“…Regulatory and management agencies generally assume that the source of E. coli is humans and warm-blooded animals. However, it has become increasingly clear that E. coli and other fecal bacterial indicators (e.g., enterococci) can persist and perhaps replicate in soil and water and on plants under certain tropical and even temperate conditions (2,4,10,14,17,19,24). Nonpoint sources generated within the watershed are generally ignored in most sanitary surveys because there is limited acceptance of the existence of significant background reservoirs of E. coli (15).…”
mentioning
confidence: 99%
“…A significant correlation has been found between coliform decay rates and solar radiation levels 7,[9][10][11][12][13][15][16][17][18][19][20][21][22][23][24] . Pathogenic microorganisms such as Giardia, Cryptosporidium, Poliovirus e Salmonella presented a higher survival in the absence of solar radiation 25 .…”
Section: Bacteria Decaymentioning
confidence: 99%